Comparing Motahari and Allameh Asgari's Views on the Meaning and Examples of ‘Affair’ - Masomeh Esmaeili (Comparative Theology)
The word affair has not been given due attention in the books of advanced theologians, but its related topics have been discussed as the nature, benefit, philosophy, or necessity of prophecy and Imamate. However, contemporary theologians have recently paid attention to this term. Motahari and Asgari have defined affairs and mentioned their examples. Affair means status and great deeds, and in terms of the Qur'an and hadiths, it means great things that the Prophet and Imams are responsible for. They are proportional. Motahari has used the term ‘affair’ in close meanings such as great works and merits. Asgari's view on the meaning of affairs is similar to Motahari's view. Of course, Askari considers the Prophet's main duty to preach the religion, which is different from the Prophet's affairs. Motahari in his various books believes that the affairs of the Prophet include religious authority, judgment, government, and guardianship. But Asgari believes that preaching the Quran, caliphate, congregational prayers, implementation of Islamic rules, and the formation of an Islamic society and a just government are the affairs of the Imam. Therefore, both theologians agree on examples such as government and religious authority as the affairs of the Imam.  Keywords: Affairs, Imam, Prophet, Askari, Motahari. IntroductionThe word affair has been used for the Prophet and Imam (AS), but there is no specific meaning for it. Therefore, there is no consensus on the cases. The earlier theologians have not had a separate discussion about the affairs of the Imam in their books. Rather, it is one of the modern theological discussions which is extracted from other Imamat topics. This issue has already been discussed in the nature, purpose, philosophy, and necessity of imamate. This term recently has been paid attention to by contemporary researchers. Motahari has mentioned three affairs for the Holy Prophet (PBUH). After that, he has said the affairs of the Imams (peace be upon them). In addition, Askari has defined affairs and has distinguished it from the main duty of a prophet.Materials and MethodsThe Great Affair is an issue that has not been discussed in the books of the past theologians by the same name. Therefore, understanding its examples requires analysis. Motahari and Asgari have paid attention to this issue and have presented its meaning and examples. They analyzed and discovered the Prophet and Imam's affairs by analyzing the related concepts, philosophy, and duties of the prophet and Imam. They expressed parts of affairs in their different books. This research studied various books by Motahari and Asgari. First, the author has obtained the meaning of Imam's affairs and has compared the views of the two theologians. Then, it has concluded a common meaning. The author also has studied the examples of Imam's affairs from the point of view of the two theologians and has compared them. In the third stage, common examples are mentioned. Research FindingsAlmighty God is doing great things in the world, and he has appointed great things for His representatives. His representatives are prophets and imams who are responsible for great works which are called affairs in this study. But the question is, what are the prophet and Imam's affairs? Motahari has stated the affairs of the Prophet and Imams (AS) in his various books:Figure 1. Prophets’ and Imam’s Affairs in Motahari’s View Then, Motahari has stated the affairs of the Imam in the continuity of prophethood:Figure 2. Affairs of the Imam in the Continuity of Prophethood in Motahari’s View As a result, Imam's affairs from the point of view of Motahari include four affairs:1.    Government2.    Religious authority3.    Judgment4.    Wilayah From Asgari's point of view, it can be said that the position of Imamate, which has been gifted to the Imam as the Caliph of God, has created some affairs for him. These affairs include the following examples:Promoting the QuranCaliphateEstablishing congregation4.    Implementation of Islamic rulesCreating an Islamic society and a just government Therefore, Askari and Motahari agree with each other in some cases and disagree in others. But the way they have expressed them is such that it can be said that all the examples mentioned by both of them are examples of affairs. DiscussionGreat Affair means the great deeds and works of the Prophet or Imam (AS). This topic is studied from the point of view of two theologians. Motahari and Asgari agree with each other on examples such as Islamic government, and religious authority, but Asgari has also specified other matters such as the propagation of the Qur'an, caliphate, implementation of Islamic rules and congregational prayers, while Motahari has also mentioned judgment and guardianship. Therefore, all these concepts can be considered as Imam's affairs. Figure 3. Comparison of Affairs in Views of Motahari and Asgari